Yield and protein composition in seeds of four buckwheat (Fagopyrum sp.) cultivars cropped in Sweden - Martin Knicky; Galia Zamaratskaia; Fredrik Fogelberg (Agricultural and Food Science, 2024)
Buckwheat (Fagopyrum sp.) is increasingly favoured for its nutritional composition and overall health benefits in Sweden. However, buckwheat cultivation in Sweden is low. This project evaluated the cultivation of four cultivars of common buckwheat in Scandinavian cropping conditions over two years, employing standard sowing methods and harvesting techniques. The results showed that a seeding rate of 200 seeds per m² was sufficient to achieve a yield comparable with other studies. There were no significant differences in germination rate and number of plants per m² between buckwheat cultivars, while significant differences were observed in maturation time and yield. The average yield of buckwheat (common or Tartary) varied from 724 kg ha-1 (“Darja”) to 3 276 kg ha-1 (“Panda”) in 2021, and from 2 587 kg ha-1 (“Kora”) to 3 133 kg ha-1 (“Tartary buckwheat”) in 2022. All buckwheat cultivars had a protein content in the seeds of approximately 110 g kg-1 of dry matter and were composed of a well-balanced amino acid profile. Our results indicate that the Swedish geographic latitude and meteorological conditions were suitable for achieving high buckwheat yields for some cultivars.